Chinese students' satisfaction of the study abroad experience - Wang, Q.; Taplin, Ross; Brown, Alistair (Emerald Group Publishing Ltd., 2011)
Purpose - Building upon McLeod and Wainwright's paradigm for rigorous scientific assessment of study abroad programs, this paper aims to use learning theory to assess mainland Chinese students' satisfaction of the Chinese Curtin Student Accounting Academic Program. Design/methodology/approach - A sample of mainland Chinese students enrolled in Curtin units were invited to complete a short survey of their perspectives of the study abroad programme. Findings - the author's results suggest that preparation for study in Australia, in addition to differences between Australia and China concerning culture and technical teaching, is essential for a mainland Chinese student to flourish in the programme. Research limitations/implications - McLeod and Wainwright's social learning theory proposes that behaviour is predicted by the expectancy that if a person behaves in a certain way that person will be rewarded by the extent that the person values the reward. The expectancy which is linked to a local control is reflected in the mainland Chinese students' preparation of studies in China. Social implications - Mainland Chinese students who feel they are better prepared for study in Australia showed higher satisfaction. Preparation is, therefore, an important factor in getting satisfaction out of the study abroad programme. Originality/value - The paper offers some helpful practical implications for managers and administrators wanting to continue the study abroad programmes. There is a clear need to convey to prospective students the need for sound preparation when students consider taking on a study abroad programme.